Generation of two human iPSC lines, HMGUi003-A and MRIi028-A, carrying pathogenic biallelic variants in the PPCS gene - Iuso, Arcangela; Zhang, Fangfang; Rusha, Ejona; Campbell, Birgit; Dorn, Tatjana; Zanuttigh, Enrica; Haas, Dorothea; Anikster, Yair; Lederer, Gabriele; Pertek, Anna; Nteli, Polyxeni; Laugwitz, Karl-Ludwig; et al. (Stem cell research, 2022)
Phosphopantothenoylcysteine synthetase (PPCS) catalyzes the second step of the de novo coenzyme A (CoA) synthesis starting from pantothenate. Mutations in PPCS cause autosomal-recessive dilated cardiomyopathy, often fatal, without apparent neurodegeneration, whereas pathogenic variants in PANK2 and COASY, two other genes involved in the CoA synthesis, cause Neurodegeneration with Brain Iron Accumulation (NBIA). PPCS-deficiency is a relatively new disease with unclear pathogenesis and no targeted therapy. Here, we report the generation of induced pluripotent stem cells from fibroblasts of two PPCS-deficient patients. These cellular models could represent a platform for pathophysiological studies and testing of therapeutic compounds for PPCS-deficiency.